STUDI KASUS: PRE DAN POST SECTIO CAESAREA ATAS INDIKASI GEMELI DAN LETAK LINTANG - Purwaningsih, Eni; Rahmawati, Lusi (Journal Healthcare Education, 2023)
Sectio caesarea is a surgical procedure to give birth to a baby through an incision in the abdominal wall (laparatomy), which is the final action for various difficulties in helping with childbirth and an alternative action for mothers who cannot or want to give birth normally. This research aims for the author to gain real experience in providing nursing care to patients with pre and post cesarean section for the indication of Gemelli Letak Lintang in the womens’s room at RSUD. The nursing diagnosis of pre section caesarea that emerged in the patient was that 2 diagnoses were not by the theory, namely acute pain related to uterine contractions and disturbance of comfort related to impaired adaptation to pregnancy. Post caesarean section nursing diagnoses that appeared in patient were 4 diagnoses by theory, namely acute pain related to physical injurious agents, impaired physical mobility related to physical unfitness, ineffective breastfeeding related to inadequate breast milk supply and risk of infection related to the effects of invasive procedures. To evaluate the results after nursing actions were carried out for 3x24 hours, the results were: of the 2 problems that appeared in pre-cesarean section patients, 2 diagnoses were partially acheved. To evaluate the results of the 4 problems that arise in post caesarean section patients, one diagnosis has been partially achieved and there are 3 diagnoses that have been achieved.